Complete alcohol abstinence increases the risk of NAFLD but not severity. A population analysis with transient elastography. (2nd January 2023) - Xiao, Jieling; Ng, Cheng Han; Chan, Kai En; Tang, Ansel Shao Pin; Teh, Readon; Ling, Abel Ho Zhi; Yong, Jie Ning; Lim, Wen Hui; Tan, Darren Jun Hao; Tan, Caitlyn; Win, Khin Maung; Bwa, Aung Hlaing; et al.
Abstract: Background & Aims: As the global prevalence of non-alcoholic fatty liver disease (NAFLD) continues to rise, ubiquity of alcohol use has also prompted discussion regarding the potential interactions between the two. This study aims to examine the effects of modest alcohol consumption on the prevalence and complications of NAFLD in a multi-ethnic population. Methods: This study analyses the 2017–2018 cycles of NHANES that examined liver fibrosis and steatosis with vibration controlled transient elastography. A coarsened exact matching was conducted to reduce confounding. Logistic regression was done with a multivariate model to assess the relationship between alcohol consumption (modest drinkers and non-drinkers) and risk of NAFLD and its complications. Results: 2, 067 individuals were found to have NAFLD and 284 NAFLD patients had a total history of alcohol abstinence. After coarsened exact matching, the prevalence of NAFLD was 49% (CI: 0.41 − 0.58) in non-drinkers and 33% (CI: 0.26 − 0.41) in modest drinkers. Non-drinkers had twice the odds of NAFLD compared to modest drinkers (OR: 1.99, CI: 1.22 − 3.22, p <.01) after adjustment for confounders. There were no significant differences in the odds of significant fibrosis, advance fibrosis, cirrhosis, cardiovascular disease and stroke between non-drinkers and modest drinkers. The odds of malignancy in non-drinkers were almost significantly less than modest drinkers (OR: 0.28, CI:0.08 − 1.02, p =.053). Conclusion: Interestingly, modest alcohol consumption is associated with decreased odds of NAFLD. Further investigations are required to examine the relationship between alcohol consumption and NAFLD and subsequently the potential impact on NAFLD management.